2016
DOI: 10.1038/srep20829
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous resonant x-ray diffraction measurement of polarization inversion and lattice strain in polycrystalline ferroelectrics

Abstract: Structure-property relationships in ferroelectrics extend over several length scales from the individual unit cell to the macroscopic device, and with dynamics spanning a broad temporal domain. Characterizing the multi-scale structural origin of electric field-induced polarization reversal and strain in ferroelectrics is an ongoing challenge that so far has obscured its fundamental behaviour. By utilizing small intensity differences between Friedel pairs due to resonant scattering, we demonstrate a time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
(41 reference statements)
1
33
0
Order By: Relevance
“…They rely on the observation of the slight difference between the diffracted intensities of Friedel or Bijvoet pairs at one given wavelength and require highly precise intensity measurements, usually performed on single crystals . Recently, the electric field driven polarization inversion was evidenced in bulk ferroelectric BaTiO 3 ‐BiZn 0.5 Ti 0.5 O 3 ceramics through a tedious measurement of the diffracted intensities for the {111} reflections near the K‐edge of the Ba atom . We have chosen a different path to benefit from the possibilities offered by REXS, making use of the tunable energy of the synchrotron to record the intensity of a Bragg reflection as a function of the energy of the scattered photons crossing an atomic absorption edge.…”
Section: Composition Thickness and Cell Parameters Of The Four Studmentioning
confidence: 99%
See 1 more Smart Citation
“…They rely on the observation of the slight difference between the diffracted intensities of Friedel or Bijvoet pairs at one given wavelength and require highly precise intensity measurements, usually performed on single crystals . Recently, the electric field driven polarization inversion was evidenced in bulk ferroelectric BaTiO 3 ‐BiZn 0.5 Ti 0.5 O 3 ceramics through a tedious measurement of the diffracted intensities for the {111} reflections near the K‐edge of the Ba atom . We have chosen a different path to benefit from the possibilities offered by REXS, making use of the tunable energy of the synchrotron to record the intensity of a Bragg reflection as a function of the energy of the scattered photons crossing an atomic absorption edge.…”
Section: Composition Thickness and Cell Parameters Of The Four Studmentioning
confidence: 99%
“…Spectra are recorded for a significant number (≈15) of reflections over a broad range of energy around the chosen edges (±60 eV). This makes the method robust against any potential experimental artefacts and much easier to perform than the comparison of very similar diffraction intensities measured for only one reflection at one wavelength …”
Section: Composition Thickness and Cell Parameters Of The Four Studmentioning
confidence: 99%
“…This principle has been used successfully by Azimonte et al [39], who observed an intensity difference of about 5% between the intensities of a reflection on multiferroic DyMn 2 O 5 after applying positive and negative electric fields, respectively. Resonant scattering has also been used to to reconstruct displacement of atoms in BaTiO 3 -based ferroelectric ceramics during polarization inversion [40]. An intensity difference of about 1% for 111 Bragg reflection was observed for two inversion-related polarization states.…”
Section: Time-resolved X-ray Diffraction With Voltage Pulses Applied mentioning
confidence: 99%
“…The measurements then have to be conducted and time-resolved, with electronic coordination between voltage pulses, detector read-out and diffractometer movements. To this extent, we adapted a setup for time-resolved diffraction, which had been previously used primarily for studying piezoelectric samples, for the synchrotron beamline P09 [41] of PETRAIII [40,[42][43][44][45]. We chose a photon energy of 8.55 keV, sufficiently far above the Fe K edge to suppress resonant scattering effects and EXAFS (extended x-ray absorption fine structure) , but close enough to provide for a significant imaginary part of the Fe scattering factor.…”
Section: Time-resolved X-ray Diffraction With Voltage Pulses Applied mentioning
confidence: 99%
See 1 more Smart Citation